Public library programs and services for midlife and beyond : expanding opportunities for a growing population - Bennett-Kapusniak, Reneé K. (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2018)
"Inspired by trends in U.S. public libraries, this book teaches librarians how to create a welcoming environment that enriches, enlightens, and engages their library's growing aging community"--